Practical methods for exploring gender relations in maize seed systems for Sub-Saharan Africa - CGIAR Research Program on Maize (2021)
The vignettes work has been applied in Kenya in 2020, with research outputs to be delivered in 2021. We expect to apply this method across other types of seed systems in India in wheat in 2021.